Blanchisseuses du propre, blanchisseurs du pur. Les mutations genrées de l’art du linge à l’âge des révolutions textiles et chimiques (1750-1820) - Raphaël Morera; Thomas Le Roux (Genre & Histoire)
This paper analyzes the gender-related changes associated with the transformation of laundering between 1750 and 1820. In this activity, the transition from organic substances to mineral substances (soda, chlorine) sheds light on the gendered competition that took place at the time of the textile and chemical revolutions. In Paris, on the Seine and Bièvre rivers, laundering had long been an exclusively female activity. Women’s appropriation of the rivers took place in the context of their accepted role in the service economy. But these practices were gradually stigmatized from the beginning of the industrial revolution. On account of the obstruction, the noise and the pollution they supposedly caused, they were supposed to be replaced by a rational, mechanical, fluid and efficient environment, defined by manufacturing technology. This environment and the rivers would thus increasingly become a male domain. Male laundrymen thus appropriated a new conception of clean-the pure–as a result of the industrial revolution.